2012
DOI: 10.3945/an.111.000919
|View full text |Cite
|
Sign up to set email alerts
|

Lifecourse Approach to Racial/Ethnic Disparities in Childhood Obesity

Abstract: Eliminating racial/ethnic disparities in health and health care is a national priority, and obesity is a prime target. During the last 30 y in the United States, the prevalence of obesity among children has dramatically increased, sparing no age group. Obesity in childhood is associated with adverse cardio-metabolic outcomes such as hypertension, hyperlipidemia, and type II diabetes and with other long-term adverse outcomes, including both physical and psychosocial consequences. By the preschool years, racial/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 138 publications
2
111
1
1
Order By: Relevance
“…49 If these behaviors are truly "obesogenic," however, families from all races and ethnicities studied need early counseling, and the findings here also underscore the likely need for culturally sensitive health behavior counseling during early infancy. Particularly actionable are the specific behaviors that may be most sensitive to culturally adapted interventions: (1) infant exposure to television and other visual media; (2) breastfeeding initiation and exclusivity; and (3) encouraging infants to finish bottles.…”
Section: Discussionmentioning
confidence: 74%
“…49 If these behaviors are truly "obesogenic," however, families from all races and ethnicities studied need early counseling, and the findings here also underscore the likely need for culturally sensitive health behavior counseling during early infancy. Particularly actionable are the specific behaviors that may be most sensitive to culturally adapted interventions: (1) infant exposure to television and other visual media; (2) breastfeeding initiation and exclusivity; and (3) encouraging infants to finish bottles.…”
Section: Discussionmentioning
confidence: 74%
“…4 Moreover, the translation of the findings across populations with different geographic and/or sociocultural backgrounds is uncertain. 6 Diet is an important determinant of the non-communicable diseases risk. 1 Food consumption has been in rapid transition during the recent decades, for example, the consumption of meat and sugar has increased in many low-and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…4 Similar environmental factors including increased built area with decreased outdoor play, increased screen time, increased intake of high-calorie foods, and caregiver food choices play a role in high childhood obesity prevalence. 5 Over the past decade, many cross-sectional and prospective epidemiologic studies have found an association between pediatric obesity and asthma. [6][7][8][9][10][11][12] A recent meta-analysis, including 6 prospective cohort studies on the effect of body weight on future risk of asthma, found a twofold increased risk in obese children compared with normal-weight children, 12 suggesting that obesity is an independent risk factor for childhood asthma.…”
mentioning
confidence: 99%